Host (Pia Grazdani, ,, 2016)
The explosive new thriller from "New York Times-"bestselling author and master of the medical thriller, Robin Cook, takes readers back to where the genre began, with "Coma" what happens when innocent hospital patients are used as medical "incubators" against their will. Lynn Pierce, a fourth-year medical student at Mason Dixon University, thinks she has her life figured out. But when her otherwise healthy boyfriend, Carl, enters the hospital for routine surgery, she doesn't know it's the last time she will see him whole again. Devastated by Carl's death, Lynn searches for answers. Convinced there's more to the story than what the authorities are willing to reveal, Lynn uses all her resources at Mason Dixon--including her initially reluctant lab partner, Edward--to hunt down evidence of medical error or malpractice. What she uncovers, however, is far more disturbing. Hospitals associated with Sentinel Healthcare, including the one attached to Mason Dixon, have unnervingly high rates of unexplained anesthetic complications and patients contracting serious and terminal illness in the wake of routine surgery. When Lynn and Edward begin to receive death threats, they know they're into something bigger than either of them anticipated. They soon enter a desperate race against time for answers before shadowy forces behind Sentinel Healthcare can put a stop to their efforts once and for all.

Weighted down: when being overweight makes you sick (Kids & obesity, , 1, 2011)
Learn about the health risks associated with being overweight and how to combat excessive weight gain.
A big problem , Right now , When you grow up , You're worth it!

An overview of pregnancy experiences: 1997 data from the Colorado Pregnancy Risk Assessment Monitoring System (PRAMS) : an update (Brief, no. 32,, 1999)
Description Not Provided

Phineas Gage: a gruesome but true story about brain science (Houghton Mifflin, Recorded Books, Inc., HarperCollins, 2007)
A science writer specializing in medicine, Fleischman tells how Gage, foreman of a railroad construction gang, survived an iron rod being blasted through his brain in 1848, and how the subsequent study of him contributed to the modern understanding of the central nervous system.

Guidelines for students developing a rash following varicella, chicken pox, vaccination (Colorado Department of Public Health and Environment, Communicable Disease Epidemiology Program, 2004)
Description Not Provided

Maternal mortality in Colorado 1990-1997 (Colorado Maternal Mortality Review Committee brief, no. 1,, 2000)
Description Not Provided

Diabetes related hospital discharges in Colorado, 1993-1995 (Health Statistics Section, 1999)
Description Not Provided

Reported influenza-associated hospitalizations 2007-2008 influenza season ([Colorado Department of Public Health and Environment, Disease Control and Environmental Epidemiology Division], 2006)
Description Not Provided

Gestational diabetes in Colorado: Pregnancy risk assessment monitoring system (PRAMS), 2006-2008 (Health watch, no. 74,, 2010)
Description Not Provided

Head injury screening and intimate partner violence: a brief report (Colorado probation research in brief, 2017/08,, 2017)
Description Not Provided

The association of prepregnancy body mass index and adverse maternal and perinatal outcomes (Health watch, no. 69,, 2009)
Description Not Provided

Smoking before, during and after pregnancy: Colorado trends (Health watch, no. 75,, 2010)
Description Not Provided

Colorado PRAMS ... surveillance report Pregnancy Risk Assessment Monitoring System (Colorado, 2000)
Description Not Provided